The strangers - Haddix, Margaret Peterson (New York, NY : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2019)
Told from separate viewpoints, Chess, Emma, and Finn Greystone, ages twelve, ten, and eight, investigate why their mother went missing and uncover their ties to an alternate world.
Keywords: Missing persons -- Fiction; Brothers and sisters -- Fiction; Family life -- Fiction; Secrets -- Fiction; Supernatural -- Fiction